Identification of New Southern Policy Narratives within ROK’s Digital Diplomacy toward ASEAN - Ratih Indraswari; Eunwoo Joo (Jurnal Ilmiah Hubungan Internasional, 2022)
Republic of Korea (ROK) shifted its policy focus toward ASEAN through the New Southern Policy (NSP). As the core foreign policy to its southern neighbors, the NSP is envisioned to ‘elevate’ ASEAN status. The partnership has been backed by institutional and bureaucratic transformation to sustain the policy. Accordingly, ROK tapped on its digital resources to support this diplomatic engagement. Digital diplomacy, therefore, is an important strategy to engage the ASEAN public. However, does ROK's digital primacy is translated well to support NSP's digital diplomacy? This paper utilizes empirical explorative qualitative primary data collection of ROK's government tweets on two levels of analysis; towards domestic and foreign audiences. The finding confirms that domestic engagement is better. However, further scrutiny shows that within domestic narratives NSP is mainly used as a political tool. Meanwhile, on external engagement, this paper argues for ROK’s digital diplomacy deficit toward ASEAN. Not only does ROK's digital diplomacy strategy lack uniformity, but it also fails to create conversation about NSP. Keywords : ASEAN, Republic of Korea, New Southern Policy, Digital Diplomacy, Twitter